Pin1 promotes degradation of Smad proteins and their interaction with phosphorylated tau in Alzheimer's disease. Issue 7 (17th November 2014) - Ueberham, Uwe; Rohn, Susanne; Ueberham, Elke; Wodischeck, Susanne; Hilbrich, Isabel; Holzer, Max; Brückner, Martina K.; Gruschka, Hildegard; Arendt, Thomas
<x xml:space="preserve">Abstract</x> Aims Neurodegeneration in Alzheimer's disease (AD) is characterized by pathological protein aggregates and inadequate activation of cell cycle regulating proteins. Recently, Smad proteins were identified to control the expression of AD relevant proteins such as APP, CDK4 and CDK inhibitors, both critical regulators of cell cycle activation. This might indicate a central role for Smads in AD pathology where they show a substantial deficiency and disturbed subcellular distribution in neurones. Still, the mechanisms driving relocation and decrease of neuronal Smad in AD are not well understood. However, Pin1, a peptidyl‐prolyl‐cis/trans‐isomerase, which allows isomerization of tau protein, was recently identified also controlling the fate of Smads. Here we analyse a possible role of Pin1 for Smad disturbances in AD. Methods Multiple immunofluorescence labelling and confocal laser‐scanning microscopy were performed to examine the localization of Smad and Pin1 in human control and AD hippocampi. Ectopic Pin1 expression in neuronal cell cultures combined with Western blot analysis and immunoprecipitation allowed studying Smad level and subcellular distribution. Luciferase reporter assays, electromobility shift, RNAi‐technique and qRT‐PCR revealed a potential transcriptional impact of Smad on Pin1 promoter. Results We report on a colocalization of phosphorylated Smad in AD with Pin1. Pin1 does not only affect Smad phosphorylation and stability but also regulates subcellular localization of Smad2 and supports its binding to phosphorylated tau protein. Smads, in turn, exert a negative feed‐back regulation on Pin1. Conclusion Our data suggest both Smad proteins and Pin1 to be elements of a vicious circle with potential pathogenetic significance in AD.